An Outbreak of dengue 2 in the Torres Strait - Griffiths, Marlene; Ritchie, Scott; Terry, Diana; Norton, Rob; Phillips, Debra (Communicable Diseases Intelligence, 2019)
On 9 December 1996, the Centre for Public Health Sciences, Brisbane, notified the Tropical Public Health Unit, Cairns, that a Torres Strait resident had tested positive for dengue serotype 2 IgM. Subsequently there have so far been 116 confirmed cases of dengue in the Torres Strait.